Market opportunities for African agriculture: A General Equilibrium examination of demand-side constraints on agricultural growth in East and Southern Africa - Diao, Xinshen; Dorosh, Paul A.; Rahman, Shaikh Mahfuzur (International Food Policy Research Institute, 2007)
This report focuses on demand-side constraints on agricultural growth and their implications for three broad alternative agricultural development strategies: promoting traditional exports, developing nontraditional exports, and increasing food staple growth. We address three major questions. First, how constraining will demand be for future agricultural growth in East and Southern Africa and, in particular, is there sufficient demand to permit agriculture to grow at a rate that can significantly reduce poverty and hunger? Second, if technological change and increase in supply are achieved, which agricultural subsectors offer the greatest potential and can become the most powerful vehicles for raising real incomes and increasing food consumption? Finally, what are the implications of reductions in marketing costs and growth linkages with nonagricultural sectors for achieving increased market demand for agricultural products? The report applies a general equilibrium framework for the analysis, focusing on seven East and Southern African countries—Madagascar, Malawi, Mozambique, Tanzania, Uganda, Zambia, and Zimbabwe—and finds that an export-led agricultural growth strategy is unlikely to generate substantial overall income growth in these countries.